The Method of Rational Distribution of Academic Disciplines in the System of Higher Education - E. Yu Borisova (Управленческое консультирование)
One of the tasks of the management of the educational institution is the development of measures aimed at improving the training of their graduates. The purpose of this article is to improve the system of planning the workload between disciplines at the university. To achieve this, an optimization model was built on the basis of system analysis and mathematical modeling. As a result, the introduction of this model in the management of the educational process will make it possible to distribute the load within the framework of one direction in such a way as to make it easier for students to master the educational material.